Retention management analysis: the turnover rate, the cost of employee turnover and employee main turnover reasons and HRM analysis : a case study in the tourism industry in Iceland - Embla Sigríður Grétarsdóttir 1982- (2016)
This research was conducted to deepen the practical understanding of the key challenges facing the human resource management in the tourism industry. The research was conducted as a case study of an organization in the tourism industry in Iceland and therefore results not generalizable. The study aimed at being interpretative and exploratory. The purpose of the study was to identify best HRM practices for effective employee retention and decreasing turnover cost. The research method was divided into the three main categories where retention management analysis was used as a guideline. These categories included measuring the turnover rate, calculating the turnover cost and analyzing employee turnover and retention reasons along with their perception of the HRM at the organization through qualitative interviews. The results showed the organization was suffering a relatively high turnover rate compared to the Icelandic market. Furthermore, the highest cost associated with employee turnover seemed to be training cost, which accounted for 70% of the total cost of the turnover. Finally, the main HRM opportunities at the organization for effective retention seemed to lie with the staffing process, training and performance management. Þessi rannsóknin var gerð með því markmiði að dýpka skilning á aðal áskorunum sem mannauðsdeildir í ferðþjónustunni þurfa að takast á við á hagnýtan hátt. Þessi rannsókn var gerð í samráði við eitt fyrirtæki í ferðþjónustunni á Íslandi og því ekki hægt að alhæfa niðurstöður. Rannsóknin var gerð með því markmiði að rannsaka og vera upplýsandi. Aðal markmið rannsóknarinnar var að bera kennsl á bestu aðferðir mannauðsstjórnunar til að halda starfsmönnum hjá fyrirtækinu og minnka þar með kostnað við starfsmannaveltu. Rannsóknin fól í sér þrjár aðferðir sem byggðar voru á “Retention Management”. Þessar aðferðir fólu í sér að mæla hlutfall starfsmannaveltunnar, reikna út kostnað við starfsmannaveluna og rannsaka ástæður fyrir starfsmannaveltunni ásamt upplifun þáttakenda af mannauðs-aðferðum ...